2012
DOI: 10.1371/journal.pone.0050543
|View full text |Cite
|
Sign up to set email alerts
|

Family-Environmental Factors Associated with Attention Deficit Hyperactivity Disorder in Chinese Children: A Case-Control Study

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders, affecting an estimated 5 to 12% of school-aged children worldwide. From 15 to 19 million Chinese children suffer from ADHD. The aim of this study was to investigate the association between family-environmental factors and ADHD in a sample of Chinese children.MethodsA pair-matched, case-control study was conducted with 161 ADHD children and 161 non-ADHD children of matching age and sex, all from 5–18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
2
7
0
1
Order By: Relevance
“…Our findings revealed that nearly 23% of the sample had experienced at least one documented type of maltreatment (physical abuse, sexual abuse, or neglect) by the adolescent (Wave 2) follow-up assessment. This rate was double that of our comparison group and is higher than national estimates (10%–20%), consistent with past research indicating that youth with ADHD are at increased risk for maltreatment (Briscoe-Smith & Hinshaw, 2006; Carroll et al, 2012; Ford et al, 2000). According to our findings, four of eight young adult functioning domains showed at least one significantly elevated measure of impairment among maltreated participants relative to nonmaltreated participants, when adjusting for demographic, prenatal, and conceptually linked baseline variables, and with control of false discovery rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings revealed that nearly 23% of the sample had experienced at least one documented type of maltreatment (physical abuse, sexual abuse, or neglect) by the adolescent (Wave 2) follow-up assessment. This rate was double that of our comparison group and is higher than national estimates (10%–20%), consistent with past research indicating that youth with ADHD are at increased risk for maltreatment (Briscoe-Smith & Hinshaw, 2006; Carroll et al, 2012; Ford et al, 2000). According to our findings, four of eight young adult functioning domains showed at least one significantly elevated measure of impairment among maltreated participants relative to nonmaltreated participants, when adjusting for demographic, prenatal, and conceptually linked baseline variables, and with control of false discovery rate.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in a large, nationally representative sample of adults, Sugaya et al (2012) found that physical abuse in childhood was associated with elevated odds of multiple adult psychiatric disorders, with ADHD showing the strongest association (see also Beers & De Bellis, 2002; Gunnar et al, 2012; Ouyang, Fang, Mercy, Perou, & Grosse, 2008). Evidence also indicates that children with ADHD are more likely to have experienced maltreatment compared to those without ADHD (Carroll et al, 2012; Ford et al, 2000), suggesting both parent–child and child–parent reciprocal causal pathways.…”
mentioning
confidence: 99%
“… 15 Although family factors may not be the key mechanism for causation of ADHD, their presence affects the entire process of the disease. 16 Therefore, good behavioral patterns need to be set up in a stable and healthy family environment for these children. For example, ineffective, inconsistent, and negligent parenting were associated with aggravating the symptoms of ADHD, including disruptive behavioral disorders, such as Conduct Disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Gender was the only demographic variable in our study, and maternal education, paternal education, maternal occupation, paternal occupation, and household income were considered as SES variables in this study. Parental education was assigned as being either compulsory education (<9 years, low level), high school education (9–12 years, middle level), or some college or advanced training (>12 years, high level) ( 24 ). Parental occupation was assigned as three levels: unemployment, manual labor, and professional.…”
Section: Methodsmentioning
confidence: 99%